SAT0230 MACROPHAGE ACTIVATION SYNDROME IN SLE AND SYSTEMIC ONSET JIA: SIMILAR OR DISSIMILAR. (2nd June 2020) - R, N.; Jain, A.; Muhammed, H.; Aggarwal, A.; Agarwal, V.; Gupta, L.; Misra, D.; Lawrence, A.; Misra, R.
Abstract : Background: Macrophage activation syndrome (MAS) is a serious complication in rheumatic disease. Fever and hyperferritinemia are common in systemic onset JIA and cytopenias are common in SLE thus recognising MAS in them is a challenge. Objectives: We compared clinical, laboratory parameters, various classification criteria for MAS, and its outcome in SLE and sJIA. Methods: Clinical and laboratory data were extracted from clinician diagnosed cases of MAS with SLE/sJIA who were admitted between 2004-2018 at a tertiary care hospital. Percentage of patients satisfying Ravelli, International consensus, HLH 2004 and criteria proposed by Parodi et al 1 were calculated. Results: Among 33 patients (18 females) with MAS 19 had SLE and 14 had sJIA. MAS was more likely to be the presenting manifestation of disease in SLE as compared to sJIA (p<0.05). There were no differences in the clinical features among these two diseases. EBV and CMV were identified in 2 patients each as the trigger for MAS. Patients with SLE had lower baseline TLC and platelet whereas patients with sJIA-MAS had significantly higher median CRP (p = 0.002), fall in TLC (p=0.012) and delta ESR/CRP ratio (p=0.02) and lower fibrinogen level (p=0.006). Neutrophil to lymphocyte ratio, Ferritin/CRP ratio and number of patients with Ferritin/ESR >80 were similar. Bone Marrow hemophagocytosis was seen in only in 21% of patients. Only 6/33 fulfilled HLH criteria but criteria meant for sJIA or SLE performed well for both diseases and majority of patients could be diagnosed using them. Treatment included steroids(100%), cyclosporine(30%), Tacrolimus(21%), cyclophosphamide(21%), etoposide(3%) and thalidomide(12%). Mortality was similar in both groups. Conclusion: MAS is more likely to be presenting manifestation in SLE compared to sJIA. Though lab parameters are significantly different in MAS associated with SLE & sJIA, criteria meant for MAS in sJIA or SLE MAS performed equally well in both diseases. References: [1]Parodi A et al, Macrophage activation syndrome in juvenile systemic lupus erythematosus: a multinational multicenter study of thirty-eight patients. Arthritis Rheum. 2009 Nov;60(11):3388-99. Disclosure of Interests: None declared